Preclinical study of reirradiation with hyperthermia in recurrent murine tumors and normal mouse skin - Charlemagne A Folefac; Priyanshu M. Sinha; Niels Bassler; Brita S. Sørensen; Michael R. Horsman (Acta Oncologica, 2025)
Background: Re-irradiation is an essential treatment option for recurrent tumours but is limited by normal tissue tolerance. Hyperthermia can enhance radiation efficacy by impairing DNA repair and improving tumor oxygenation; however, limited preclinical data are evaluating its combination with re-irradiation in recurrent tumor settings and normal skin.